Correlation between body mass index and the results of the treatment of iron deficiency anemia in pregnant women - Diana Turlacova; Ianos Coretchi (The Moldovan Medical Journal, 2019)
Background: Iron deficiency anemia (IDA) is a hematologic syndrome characterized by the deregulation of hemoglobin synthesis due to iron deficiency. During pregnancy, there is an increase of about six times of iron. A correlation between body mass index (BMI) and hemoglobin (Hb) in pregnant women with IDA during the treatment with “Sorbifer Durules” (SD) was evaluated. Material and methods: A retrospective, cohort study. 40 medical cards of pregnant women diagnosed with IDA during the pregnancy and who were treated with SD: one tablet 2 times per day, were studied. The BMI and Hb levels were assessed in each trimester of pregnancy. The dynamic of Hb values was determined: ΔHbII-I – the difference between Hb values of the 2nd and of the 1st trimesters, ΔHbIII-II – the difference between Hb values of the 3rd and of the 2nd trimesters. Statistics: Pearson’s correlation coefficient. Results: IDA was diagnosed in 15 out of 40 pregnant women in the 1st trimester of pregnancy (IDA1), in 19 – in the 2nd trimester (IDA2), in 6 – in the 3rd trimester (IDA3). 7 pregnant IDA1 with normal body weight (BMI = 18,5-25 kg/m2 ) had ΔHbII-I=14,28 g/l, 8 pregnant IDA1 with grade I obesity (BMI=30-35 kg/m2 ) had ΔHbII-I=26,12 g/l. Pearson correlation coefficient between BMI in the 1st trimester of pregnancy and ΔHbII-I in pregnant IDA1: r=+0,617, p=0,014. The associations between BMI and ΔHb in pregnant IDA2 and IDA3 were negligible. Conclusions: There is a substantial and significant association between BMI in pregnant women who developed IDA in the 1st trimester and Hb increase during the treatment with SD.